THE INFLUENCE OF FINANCIAL LITERACY AND LIFESTYLE ON FINANCIAL MANAGEMENT BEHAVIOR OF CAREER WOMEN IN PITU RIAWA DISTRICT - Rahmayanti, Riska; Rukiah; Purnamasari, Rini (Institut Agama Islam Negeri Parepare, 2023)
In the era of globalization and rapid technological development, career women are faced with various challenges in managing their personal finances. Financial Literacy, which includes knowledge and understanding of basic financial concepts, as well as Lifestyle which reflects consumption patterns and individual priorities, are believed to play an important role in forming healthy financial management behavior. The aim of this research is to determine whether there is an influence between Financial Literacy and Lifestyle on Financial Management Behavior and whether both influence simultaneously. The research method used is quantitative with a descriptive approach using data collection techniques, namely primary data in the form of questionnaire data and secondary data obtained indirectly which is tested using descriptive analysis tests, data feasibility tests, classical assumption tests, hypothesis tests, and multiple linear regression analysis. The research results show that: (1) Financial Literacyhas a positive and significant effect on Financial Management Behavior, this is proven by the calculated t value > t table or 4.563 > 1.998 with a significance level of 0.000 < 0.05. (2) Lifestyle has a negative and significant effect on Financial Management Behavior, this is proven by the calculated t value < t table or -5.063 < 1.998 with a significance level of 0.000 < 0.05. (3) Financial Literacy and Lifestyle simultaneously influence Financial Management Behavior, this is proven by the Fcount value of 22.809 > Ftable 3.15 and a significant value of 0.000 < 0.05.